2020
DOI: 10.1001/jamanetworkopen.2020.10185
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health Outcomes Among Frontline and Second-Line Health Care Workers During the Coronavirus Disease 2019 (COVID-19) Pandemic in Italy

Abstract: Health care workers (HCWs) involved in the coronavirus disease 2019 (COVID-19) pandemic are exposed to high levels of stressful or traumatic events and express substantial negative mental health outcomes, 1 including stress-related symptoms and symptoms of depression, anxiety, and insomnia. In this cross-sectional study, we report on mental health outcomes among HCWs in Italy. Methods This cross-sectional, web-based study collected data between March 27 and March 31, 2020, using an online questionnaire spread … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

115
699
36
56

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 725 publications
(974 citation statements)
references
References 7 publications
115
699
36
56
Order By: Relevance
“…Also, the constant fear of contagion leads to obsessive thoughts ( Brooks et al, 2020 ), increasing the progressive closure of the person and reducing social relationships. In line with these results, Rossi et al (2020) evaluated mental health outcomes among HCWs in Italy during the pandemic, confirming a high score of mental health issues, particularly among young women and front-line workers. Furthermore, Spoorthy et al (2020) conducted a review on the gendered impact of Covid-19 and found that 68.7–85.5% of medical staff is composed of women, and the mean age ranged between 26 and 40 years.…”
Section: Covid-19 and At-risk Populations: Psychological And Social Isupporting
confidence: 68%
“…Also, the constant fear of contagion leads to obsessive thoughts ( Brooks et al, 2020 ), increasing the progressive closure of the person and reducing social relationships. In line with these results, Rossi et al (2020) evaluated mental health outcomes among HCWs in Italy during the pandemic, confirming a high score of mental health issues, particularly among young women and front-line workers. Furthermore, Spoorthy et al (2020) conducted a review on the gendered impact of Covid-19 and found that 68.7–85.5% of medical staff is composed of women, and the mean age ranged between 26 and 40 years.…”
Section: Covid-19 and At-risk Populations: Psychological And Social Isupporting
confidence: 68%
“…In addition, they were also invited through WhatsApp, email and verbal reminders among each other. Sample size was calculated based on the precision of 0.05, level of confidence of 95%, and prevalence of depression (24.73%), anxiety (19.80%) and stress (21.90%) from a cross-sectional study among healthcare workers in the midst of the COVID-19 pandemic in Italy [ 12 ], and the results were 419, 246, and 264 samples, respectively. All participants participated on a voluntary basis, received information about the procedure of the investigation and gave their online consent before participation.…”
Section: Methodsmentioning
confidence: 99%
“…Multiple studies related to mental health have been conducted among healthcare workers. For instance, Rossi et al (2020) conducted a cross-sectional study in March 2020 immediately preceding the COVID-19 contagion peak in Italy through an online questionnaire among all healthcare workers in Italy [ 12 ]. A total of 1379 healthcare workers completed the questionnaire.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During pandemics, healthcare staff is exposed to contagious materials, high levels of An IP model for assignment in tele-psychoterapy during Covid-19 3 stress, sleep deprivation, or compassion fatigue [50,8,45]. Thus, health workers have a higher probability and disposition to develop mental health anguish and disorders [53]. An important component to effectively alleviate pandemic-related distress is to prioritize psychological intervention for healthcare professionals [48,17].…”
Section: Introductionmentioning
confidence: 99%